Étude génétique de la représentation des femmes dans Un homme pareil aux autres de René Maran - Tina Harpin (Institut des textes & manuscrits modernes (ITEM), 2021)
Un homme pareil aux autres is a novel inspired by the real life of René Maran, rewritten from the 1920s until its final version in 1947. In fact, it is a romance novel whose sentimentality has received little attention or was squarely belittled. This article analyses what is at stake in this sentimental writing by studying Jean Veneuse’s relationship to women and the evolution of their portrayal in the different versions of the text. Un homme pareil aux autres is the novel of a sentimental dandy in which certain sexist prejudices are expressed whereas, on the other hand, certain racist prejudices are fought against. Veneuse fails to express the condition of black women or white women, all seen in the light of the idealized image of the beloved Andrée Marielle. Another white woman, Clarisse, remains in the shadows as she witnesses the indefensible behavior of the narrator who presents himself as a bashful lover. Her status is as ambivalent as the one of the African women characters and remains awkward in the various versions of the novel.